Educational Propensities: Learning, Teaching, Mediating - Espinoza Vásquez, Rodrigo (2024)
This article aims to investigate the inclination to mediate that arises in educational experiences, based on two previous conceptualizations: the inclination to learn and to teach. Referring to this topic implies making visible the practices that occur in educational activities. It starts from the conception that education is the creation of possible relationships and extends beyond the school. The inclination to mediate is compared to the weaving of a loom, where the boundaries between learning and teaching blur. The importance of patience and aesthetic sense in the act of mediating is mentioned, as well as the need to let go of fear. Mediation is approached as an act of tenderness, patience, and compassion, highlighting the importance of allowing learning and respecting the freedom of the learner. In conclusion, it is emphasized that the inclination to mediate involves expanding educational boundaries, moving more towards chance than causality. The importance of empathy in mediation relationships is highlighted, and the shift in disposition towards a listening relationship and availability to the other is underscored.